Business diversification and innovation as pathways to financial viability in pesantren - Hafidh, Zaini; Kadarsah, Deni; Raspatiningrum, Liris; Nurdin, Nurdin; Suri, Atikah; Oktarialdi Pratama , Ignasius (Universitas Jambi, Indonesia, 2026)
This study examines the role of business diversification and innovation in enhancing the financial sustainability of pesantren (Islamic boarding schools) in Indonesia. Using a qualitative case study approach, data were collected from Pondok Pesantren Ar-Risalah Cijantung IV in West Java through interviews, document analysis, and participant observation. The findings reveal that diversified business units, such as aquaculture, agriculture, retail services, and mineral resource partnerships, significantly contribute to financial viability. These initiatives help reduce dependency on tuition fees and philanthropic contributions, ensuring continued operation and educational quality. Challenges such as limited human resources, regulatory compliance, and market competition are identified, requiring strategic management to mitigate risks. The study emphasizes that innovation in business practices, combined with strategic partnerships and enhanced governance, is essential for long-term sustainability. This research provides valuable insights for pesantren leaders and policymakers on how to achieve financial independence while maintaining educational excellence.